Strategic planning, local authorities and territorial development: an experience of the Euro-Latin american co-operation in Colombia - Tassara, Carlo (Iberoamerican Journal of Development Studies, 2013)
This paper reasons about the importance of the strategic planning for territorial development and on the contribution of the Euro-Latin American co-operation to the strengthening of the capacities of local authorities in Colombia. Within this context, the paper presents as case study the Project «European Union and Latin America for Welfare Integrated Policies» implemented between 2009 and 2013 under the URB AL Regional Programme. The Project, led by the Italian Region Emilia Romagna, has established a network of local authorities representing five countries (Argentina, Brazil, Colombia, Italy and Spain) for the exchange of best practices and the support to public policies for territorial development and local governance.